The Guatemala-Penn Partners: An Innovative Inter-Institutional Model for Scientific Capacity-Building, Healthcare Education, and Public Health - Paniagua-Avila, Maria Alejandra; Messenger, Elizabeth; Nelson, Caroline A.; Calgua, Erwin; Barg, Frances K.; Bream, Kent W.; Compher, Charlene; Dean, Anthony J.; Martinez-Siekavizza, Sergio; Puac-Polanco, Victor; Richmond, Therese S.; Roth, Rudolf R.; et al. (Frontiers in Public Health, 2017)
Population health outcomes are directly related to robust public health programs, access to basic health services, and a well-trained health-care workforce. Effective health services need to systematically identify solutions, scientifically test these solutions, and share generated knowledge. The World Health Organization (WHO)’s Global Healthcare Workforce Alliance states that the capacity to perform research is an essential factor for well-functioning public health systems. Low- and middle-income countries have greater health-care worker shortages and lower research capacity than higher-income countries. International global health partnerships between higher-income countries and low-middle-income countries aim to directly address such inequalities through capacity building, a process by which human and institutional resources are strengthened and developed, allowing them to perform high-level functions, solve complex problems, and achieve important objectives. The Guatemala–Penn Partners (GPP) is a collaboration among academic centers in Guatemala and the University of Pennsylvania (Penn), in Philadelphia, Pennsylvania that echoes the vision of the WHO’s Global Healthcare Workforce Alliance. This article describes the historical development and present organization of the GPP according to its three guiding principles: university-to-university connections, dual autonomies with locally led capacity building, and mutually beneficial exchanges. It describes the GPP activities within the domains of science, health-care education, and public health, emphasizing implementation factors, such as sustainability and scalability, in relation to the guiding principles. Successes and limitations of this innovative model are also analyzed in the hope that the lessons learned may be applied to similar partnerships across the globe.